Lamp emission and quartz sleeve modelling in slurry photocatalytic reactors - Boyjoo, Y; Ang, Ming; Pareek, Vishnu (Pergamon, 2014)
Modelling of incident radiation intensity in a reaction medium or at catalyst surface is a necessity for kinetics modelling of pollutant degradation in photocatalytic reactors. In slurry photoreactors, the incident radiation within the reacting medium is calculated via the radiative transport equation (RTE) which considers the absorption and scattering of light due to the catalyst particles. As a result, a proper lamp emission model is required so as to obtain boundary conditions of the incident radiation entering the reacting medium. In this paper, we examine the validity of line, surface and volumetric source models at describing the incident radiation around a UV lamp. We then examine the effects of different lamp length to lamp radius ratios (2L/rlamp) and lamp ageing on the lamp emission model, with respect to the more descriptive and accurate volume source model. Finally, computational fluid dynamics (CFD) simulations are performed to determine the effect of light reflection, refraction and absorption at the air–quartz–water interfaces on incident radiation entering the reaction medium, for three quartz tube radius to lamp radius ratios (rquartz/rlamp) and two typical quartz tube thicknesses. The results obtained in this study are conveniently presented in dimensionless form and could be used as correction factors in the setting up of the radiation boundary condition in the modelling of cylindrical slurry photocatalytic reactors.